VD_FINDINFO AI 31/11 - 238/2012 vom 15. Mai 2012 - VD Tribunal cantonal (2012)
RÉVISIONDÉCISION, RECONSIDÉRATION, DEGRÉ DE L'INVALIDITÉ | 28 al. 2 LAI, 28a LAI, 4 al. 1 LAI, 16 LPGA, 17 LPGA, 53 al. 2 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 88a al. 1 RAI